Alginate-based composites for environmental applications: a critical review. Issue 4 (16th February 2019) - Wang, Bing; Wan, Yongshan; Zheng, Yuling; Lee, Xinqing; Liu, Taoze; Yu, Zebin; Huang, Jun; Ok, Yong Sik; Chen, Jianjun; Gao, Bin
Abstract: Alginate-based composites have been extensively studied for applications in energy and environmental sectors due to their biocompatible, nontoxic, and cost-effective properties. This review is designed to provide an overview of the synthesis and application of alginate-based composites. In addition to an overview of current understanding of alginate biopolymer, gelation process, and cross-linking mechanisms, this work focuses on adsorption mechanisms and performance of different alginate-based composites for the removal of various pollutants including dyes, heavy metals, and antibiotics in water and wastewater. While encapsulation in alginate gel beads confers protective benefits to engineered nanoparticles, carbonaceous materials, cells and microbes, alginate-based composites typically exhibit enhanced adsorption performance. The physical and chemical properties of alginate-based composites determine the effectiveness under different application conditions. A series of alginate-based composites and their physicochemical and sorptive properties have been summarized. This critical review not only summarizes recent advances in alginate-based composites but also presents a perspective of future work for their environmental applications.